Amplified optical nonlinearity in a self-assembled double-strand conjugated porphyrin polymer ladder. - Screen, T; Thorne, JR; Denning, R; Bucknall, D; Anderson, H (2002)
Addition of 4,4'-bipyridyl to a solution of a meso-meso butadiyne-linked conjugated zinc porphyrin polymer in chloroform results in self-assembly of a double-strand ladder complex. Excess ligand causes this duplex to dissociate into single strands. These binding processes were elucidated by near-IR and NMR titrations, as well as by gel permeation chromatography and small-angle neutron scattering. Ladder-making and -breaking are highly cooperative, with Hill coefficients of 3.0 and 3.7, respectively. Self-assembly of the ladder holds the pi-system in a planar conformation, enhancing the conjugation, resulting in a red-shift and intensification of the Q-band. Both the real and imaginary parts of the third-order susceptibility per macrocycle are amplified by ladder formation, as revealed by degenerate four-wave mixing measurements at 1064 nm. At this wavelength, the double-strand polymer complex has |chi(3)xyyx| = 6.0 x 10-17 m2 V-2 per macrocycle, compared with 6.6 x 10-18 m2 V-2 for the single-strand polymer under the same conditions.